High Performance of Commercial PAC on the Simultaneous Desulfurization and Denitrification of Wastewater From a Coal-Fired Heating Plant - Liu, Jiancong; Wang, Ying; Wang, Yangyang; Wang, Zhigang; Wang, Xiaoshu; Kong, Fanrong; Yan, Zheng; Li, Tong; Wang, Lei (Frontiers in Chemistry, 2022)
The flue gas desulfurization wastewater was highly-saline and refractory to be recycled in the desulfurization process of the coal-fired heating plant. Given that waste heat was abundant in coal-fired heating plants, a thermal treatment method was developed to synchronously remove sulfate and nitrate from the wastewater, with the production of chemical-grade natroalunite and recycled water. The results showed that sulfate and nitrate were 50.3 g/L and ten g/L in the wastewater, and only removed by 2.8% and 9.1% after direct treatment at 270 oC for seven h, but heavily removed by 99.3% and 99.9% with the addition of commercial poly aluminum chloride. Mass balance summarized that the treatment of one-ton wastewater needed 0.1-ton PAC and produced 0.11-ton natroalunite and 0.92 ton recycle water. The removal of sulfate and nitrate was predominated by the precipitation reaction of sulfate as natroalunite and the redox reaction between nitrate and organics, respectively. The thermodynamic analysis demonstrated that the precipitate reaction occurred at 45 oC and accelerated in the temperature range of 45-270 oC, but became slow by the decrease of sulfate and Al concentrations in wastewater. Other four reagents were also used for wastewater treatment in comparison with PAC and showed the performance in the following order: PAC > citrate calcium > limestone > subacetate aluminum > citrate ferric. Such a method provided a practical route to treat flue gas desulfurization wastewater without generating secondary waste.